Wealth preferences and wealth inequality: Experimental evidence - Nobuyuki Hanaki; Yuta Shimodaira (Osaka University, Institute of Social and Economic Research (ISER), 2024)
Some researchers claim that a preference for wealth accumulation is the main cause of the long-run stagnation of the Japanese economy. A theoretical implication of people having such a preference is the widening of wealth inequality. We experimentally test this theoretical prediction by inducing wealth preference in the laboratory. When all the participants are considered, our results provide limited support for the prediction that wealth inequality widened only in one of the four conditions we considered. However, if we focus on the participants who have followed conditionally optimal paths more closely than others, the widening wealth inequality is observed in all the conditions.
Keywords: C91; E21; E71; 330; ealth preferences; experiment; consumption-saving decision; dynamic optimization